Chalcogenides by Reduction of their Dioxides in Ultra-Alkaline Media - Albrecht, Ralf; Ruck, Michael (Angewandte Chemie International Edition, 2021)
The reaction of chalcogen dioxides ChO2 (Ch=Se, Te) with As2O3 in a 30 molar KOH hydroflux at about 200 °C yielded crystals of potassium trichalcogenides K2Ch3 with dimensions up to 2 cm. Arsenic trioxide acts as electron donor and is oxidized to arsenate(V). The new heterochalcogenide anion (TeSe2)2− formed when starting from SeO2 and TeO2 simultaneously. The compound K2TeSe2 crystallizes isostructural to K2S3 and K2Se3. The unexpected redox reaction as well as the precipitation of hygroscopic compounds from an aqueous solution are attributed to a strongly reduced activity of water. The reactions were studied by Raman and UV/Vis spectroscopy. Depending on the concentration of As2O3, colorless monochalcogenide Ch2− or orange Se22− and purple Te22− anions are dominating the solutions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: crystal structure; hydroflux; selenium; spectroscopy; tellurium